Manifestations of cohesion and coherence in the poem “The Lightning and the Rain” by Obaid ibn al-Abras - djamila.grine, djamila.grine (El Omda in Linguistics and Discourse Analysis, 2024)
The pre-Islamic environment was the engine and support for the poets, so the poetry of nature took a prominent place in the Arabic poem, which made the poets describe everything that their eyes fell upon, describing the moving nature and the rigid nature, thus drawing original artistic paintings, taking care of the smallest details, leaving nothing but recording it In their poetry, , and was closest to their souls, emotions, and conscience. We chose the poem “Description of Lightning and Rain” by Ubaid Ibn al-Abras to study consistency and harmony in it, in order to reach the extent of their contribution to the objective coherence of the text.